AB0929 Neutrophil/lymphocyte Ratio (NLR), Platelet/lymphocyte Ratio (PLR) Were Useful Markers in Assessment of Inflammatory Response in Aosd Patients. (15th July 2016) - Lee, W.S.; Choi, Y.-J.; Hong, M.-J.; Lee, C.-H.; Lee, M.S.; Lee, S.-I.; Cheon, Y.-H.; Yoo, W.-H.
Abstract : Background: Both neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte (PLR) are reported to be increased in various inflammatory diseases, but there clinical significance in adult onset still disease (AOSD) remains unclear. Objectives: The aim of the present study was to evaluate NLR and PLR as a inflammatory marker in AOSD. Methods: The medical records of 23 AOSD patients and age, sex-matched 25 healthy individuals were retrospectively reviewed. NLR, PLR between AOSD patients and healthy controls were compared, and correlation between these indexes and clinical characteristics were analyzed. Exclusion criteria included active infection and/or the presence of any hematological, cardiovascular or metabolic disorder. Results: The NLR and PLR were found to be significantly higher in AOSD patients when compared to the healthy control (NLR: 10.67± 6.73 vs 2.05±1.07, p<0.001, PLR: 255.78±107.22 vs 128.10 ±42.60, p<0.001). The NLR and PLR were decreased significantly after treatment (4.67±3.22, 196.84±78.54). NLR was positively correlated with erythrocyte sedimentation rate (ESR)(r=0.612, p<0.001), C-reaction protein (CRP)(r=0.597, p<0.001) and ferritin (r=0.552, p<0.001). PLR was positively correlated with ESR (r=0.648, p<0.001), CRP (r=0.536, p<0.001) except ferritin (r=0.33, p=0.025). Conclusions: NLR, PLR, together with other serum inflammatory markers, were proving as significant clinical tools which could be used as biomarkers for inflammatory response of disease activity in AOSD patients. Disclosure of Interest: None declared